2023
DOI: 10.1038/s41419-023-06045-y
|View full text |Cite
|
Sign up to set email alerts
|

The diversified role of mitochondria in ferroptosis in cancer

Yu’e Liu,
Shiping Lu,
Lei-lei Wu
et al.

Abstract: Ferroptosis is a form of regulated cell death induced by iron-dependent lipid peroxidation, and it has been studied extensively since its discovery in 2012. Induced by iron overload and ROS accumulation, ferroptosis is modulated by various cellular metabolic and signaling pathways. The GSH-GPX4 pathway, the FSP1-CoQ10 pathway, the GCH1-BH4 pathway, the DHODH-CoQH2 system and the sex hormones suppress ferroptosis. Mitochondrial iron metabolism regulates ferroptosis and mitochondria also undergo a morphological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 156 publications
0
15
0
Order By: Relevance
“…1(f) exhibited a wide absorption attributed to PDA N–H/O–H stretching vibrations (3135–3650 cm −1 ), with characteristic peaks at 1510 cm −1 and 963 cm −1 corresponding to the –CO and –CH stretching of Cur. 37,38 The optical absorption spectrum displayed broadly absorptive properties and a Cur peak at 440 nm ( Fig. 1(g) ).…”
Section: Resultsmentioning
confidence: 99%
“…1(f) exhibited a wide absorption attributed to PDA N–H/O–H stretching vibrations (3135–3650 cm −1 ), with characteristic peaks at 1510 cm −1 and 963 cm −1 corresponding to the –CO and –CH stretching of Cur. 37,38 The optical absorption spectrum displayed broadly absorptive properties and a Cur peak at 440 nm ( Fig. 1(g) ).…”
Section: Resultsmentioning
confidence: 99%
“… 39 The expression level of GCH1 largely determines the degree of cell resistance to ferroptosis, and downregulation of GCH1 promotes peroxidation accumulation and ferroptosis in cells. 40 Glutathione-specific gamma-glutamylcyclotransferase 1 (CHAC1), a component of the unfolded protein response pathway, plays a key role in oxidative stress-induced ferroptosis by regulating glutathione depletion. 41 NADPH oxidases (NOXs) are a family of ROS-producing enzymes, and among the NOX isoforms, NOX4 is a major isoform in astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria serve a diversified role in the process of ferroptosis, iron metabolism and the oxidative phosphorylation pathway, and reactive oxygen species (ROS) are highly involved in ferroptosis ( 70 ). It has been demonstrated that the typical metabolic activities of the mitochondria, including tricarboxylic acid cycle and electron transport chain activities, are required for cellular lipid peroxide production in ferroptosis induced by cysteine (Cys) deprivation, but not in that induced by inhibiting GPX4 ( 57 , 71 ).…”
Section: Mechanism Of Ferroptosismentioning
confidence: 99%